An economic evaluation model for charging stations of EVs in distribution networks with compensation devices and constraints - Yu, Lu; Chao, Lu; Yihua, Liu; Menghua, Deng; Yanjun, Chen; Ruochen, Duan (Frontiers in Energy Research, 2024)
With the increasing penetration level of electric vehicles (EVs) in distribution networks, the limited capacity of distribution networks becomes the bottleneck for EV integration. Considering the difficulties of capacity expansion in distribution networks, especially in the large cities, integrating EV with photovoltaic (PV) generation systems and battery energy storage systems becomes a possible technical solution for distribution networks. However, the uncertainties in the PV generation systems and EV loads brings difficulties to the planning and operating methods for such systems. This paper presents an evaluation model that simulates the uncertainties of EV and PV power generation systems using a large number of stochastic scenarios generated by the Monte Carlo method, to assess the revenue of various operators under multiple possible scenarios. Multiple operation constraints were considered in the proposed method, including voltage deviations, capacity limitation of the transformer, the satisfaction of EV owners and other physical constraints. In order to accelerate the evaluation process of the EVs, the Distflow equations for distribution networks was applied in the proposed evaluation model. The results of case studies indicate that the maximum capacity of EVs with different scenarios can be calculated by the proposed model.